2018
DOI: 10.1093/abm/kay006
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Linking Childhood SES and Adult Health Behaviors and Psychological Resources in Black and White Men

Abstract: Positive parenting in adolescence was an important pathway in understanding associations among childhood SES and health behaviors and psychological resources in adulthood. Low childhood SES was prospectively associated with healthier behaviors and greater psychological resources in part through more positive parenting in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Two participants were missing scores on some components and thus have prorated psychological resource scores based on the components with available data. The composite has good internal consistency reliability (full sample α=.87; α=.89 in Black men and α=.85 in White men); prior work in this sample has shown measurement invariance for a psychological resource composite including purpose in life, optimism, self-mastery, and self-esteem across race (37).…”
Section: Methodsmentioning
confidence: 87%
“…Two participants were missing scores on some components and thus have prorated psychological resource scores based on the components with available data. The composite has good internal consistency reliability (full sample α=.87; α=.89 in Black men and α=.85 in White men); prior work in this sample has shown measurement invariance for a psychological resource composite including purpose in life, optimism, self-mastery, and self-esteem across race (37).…”
Section: Methodsmentioning
confidence: 87%
“…The Hollingshead measure is one of the most frequently used measures of socioeconomic position and has demonstrated good interrater reliability in previous research (Cirino et al, 2002). The Hollingshead in its original scoring system continue to be used as an estimate of SES across health research (Arentoft et al, 2015;Bava et al, 2018;Boylan et al, 2018;Bublitz et al, 2016;Daepp and Arcaya, 2017;Harris et al, 2014;Heptulla et al, 2016;Hur et al, 2015;Matthews et al, 2014;Mogi et al, 2019;Seyrek et al, 2017;Turkheimer et al, 2015;Turkheimer et al, 2003;Valenzuela et al, 2019). However, given more recent studies that define SES as education, income, or occupation alone (Brito et al, 2016;Merz et al, 2017;Noble et al, 2015a;Noble et al, 2015b;Noble et al, 2012;Noble et al, 2007;Noble et al, 2005;Noble et al, 2006), and the suggestion that occupation is one of the best estimates of SES as it reflects power, income, and education (https://macses.ucsf.edu/research/ socialenviron/occupation.php), we also re-coded our occupation variable using an updated system (O*NET government codes [https://www.onetcenter.org/overview.html] based off the standard occupation classification [https://www.bls.gov/soc/]) (Choi et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Life satisfaction can also represent a more stable and diversified measure of the lives of middle-aged and elderly people [ 55 ]. Higher adult SES, support for family members and other aspects of life may increase the life satisfaction of middle-aged and elderly people, moderate the adverse effects of childhood, and thus improve their physical and psychological status [ 57 , 58 ]. Studies have shown that life satisfaction is particularly strongly associated with health [ 59 ].…”
Section: Discussionmentioning
confidence: 99%